Integration of broth extraction and recycling scheme to bio- ethanol production from water hyacinth - ., Taslim; Bani, Okta; ., Iriany (International Journal of Engineering and Technology, 2019)
Bioethanol production from water hyacinth (Eichhornia crassipes) has been progressively studied these recent years. However, the technology was still inapplicable because of low final ethanol concentration which leads to uneconomic process. Since acquiring broth with high ethanol concentration by common processing scheme is quite unlikely for this type of biomass, other approaches must be taken. Combining several strategies ever studied, this study employed salt enhanced extraction and direct broth recycling as the main strategies to improve the final concentration. The aim of this study, thereafter, was to evaluate the compatibility and implications of these processes integration. In this research, pre-blended and dried water hyacinth was subjected to dilute acid pretreatment followed by enzymatic hydrolysis, fermentation, and extraction. Broth recycling was done by directly replacing a portion of enzyme with filtered broth. Results showed that extraction enhances ethanol production, while recycling trades ethanol yield for increase in level. Â Â